PEMBERDAYAAN PEMBUATAN SABUN CUCI PIRING BERBAHAN HERBAL ANTIMIKROBA PADA IBU-IBU RUMAH TANGGA DI KABUPATEN JEMBER - Lindawati Setyaningrum; Sholihatil Hidayati; Wima Anggitasari; Aliyah Purwanti; Diah Yuli Pangesti; Khrisna Agung Cendekiawan; Iski Weni Pebriarti; Shinta Mayasari; Dina Trianggaluh Fauziah; Nafisah Isnawati; M. Rofik Usman; Dhina Ayu Susanti (Jurnal SADEWA, 2024)
Soap is a material used for washing clothes, furniture, the body, etc. which is made from a mixture of alkali and triglycerides from fat. However, as time goes by, today's people are using ready-to-use sponges and washing soap in various forms and their respective advantages. Currently, many dishwashing soaps use herbal ingredients as their active substances. Coriander seeds and orange oil are herbal ingredients that can be used as antibacterial ingredients which can be used as active ingredients in making dishwashing soap. The village community's lack of knowledge regarding herbal ingredients and how to make dish soap has closed down business opportunities in Kopang Kebun Hamlet, Kemuning Lor Village, Arjasa District, Jember Regency. Therefore, village communities need training to process these herbal ingredients into products that are safe for the environment. The aim of this program for making liquid dish washing soap is to empower the women of Kopang Kebun Hamlet, most of whom are housewives, so that with this outreach, the community can make their own liquid soap to meet their daily needs and can also be used as a home industry.